A novel graphene zinc composite heavy-duty anticorrosion coating and preparation method thereof
The novel graphene zinc composite coating addresses cracking issues by using hollow nano zinc powder and alumina to create a lightweight, uniformly dispersed structure that prevents galvanic corrosion, improving crack resistance and durability.
Patent Information
- Application Number
- CN202411413705.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Traditional graphene zinc composite heavy-duty anti-corrosion coatings are prone to cracking due to high zinc powder content and uneven stress distribution, leading to increased density and weight, which exacerbates internal stress and cracking during construction and drying.
A novel graphene zinc composite anti-corrosion coating using hollow nano zinc powder and alumina powder, combined with graphene, to form a uniform and lightweight coating structure that reduces stress concentration and prevents galvanic corrosion, enhancing mechanical strength and corrosion resistance.
The coating exhibits improved crack resistance, extended service life, and enhanced durability by reducing weight and internal stress, while maintaining effective corrosion protection through a uniform dispersion of zinc ions and insulation between graphene and zinc.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coating preparation, and more specifically, to a novel graphene zinc composite heavy-duty anti-corrosion coating and a preparation method thereof. Background Art
[0002] Heavy-duty anti-corrosion coatings are high-performance coatings relative to conventional anti-corrosion coatings. They can be used in relatively harsh corrosive environments and have a longer protection period than conventional anti-corrosion coatings. In recent years, research in the field of heavy-duty anti-corrosion coatings has made significant progress. On the basis of traditional anti-corrosion coatings, a series of new varieties with excellent performance have emerged. Among them, graphene zinc composite heavy-duty anti-corrosion coatings, as a commonly used heavy-duty anti-corrosion coating, have been widely used in the field of heavy-duty metal anti-corrosion due to their excellent corrosion resistance. The core of this coating is that graphene has a large specific surface area and good dispersibility, and can form a uniform physical layer in the coating. This isolated layered structure has a good physical shielding effect on the diffusion of water, oxygen and ions, effectively blocking the penetration of these corrosive media. At the same time, zinc powder, as a filler, together with graphene, forms a dense coating structure, further enhancing the physical shielding properties of the coating.
[0003] In the related art, for example, the application number 201810347478.X discloses a method for preparing an epoxy zinc ene heavy anti-corrosion coating, which belongs to the technical field of coating preparation. The present invention first grinds and compounds graphene and zinc powder to obtain a graphene-zinc composite powder, and modifies the surface of the graphene-zinc composite powder with toluene diisocyanate, which can effectively prevent the agglomeration of graphene and zinc powder in the resin, greatly improve the dispersion performance of the composite powder in the resin, so as to give full play to the anti-corrosion effect of the graphene composite powder and enhance the anti-corrosion property of the epoxy resin coating.
[0004] However, in traditional graphene zinc composite heavy-duty anti-corrosion coatings, the zinc powder content is usually high and the zinc powder density is large. The high zinc content increases the density of the coating, and the weight of the coating of the same thickness also increases accordingly. During the construction process and after drying, the high-density coating is prone to cracking due to the uneven distribution of internal stress. Summary of the invention
[0005] In order to improve the defect of the coating in the related art that it is easy to crack after construction, the present application provides a novel graphene zinc composite heavy-duty anti-corrosion coating and a preparation method thereof.
[0006] The novel graphene zinc composite heavy-duty anti-corrosion coating provided in this application adopts the following technical solution:
[0007] A novel graphene zinc composite heavy-duty anti-corrosion coating comprises the following raw materials in parts by weight:
[0008] Epoxy resin 30-50 parts;
[0009] 20-30 parts of graphene-zinc composite powder;
[0010] 10-20 parts of filler;
[0011] Dispersant 2-5 parts;
[0012] 15-30 parts of solvent;
[0013] 1-3 parts of leveling agent;
[0014] The graphene-zinc composite powder is obtained by ball milling and drying graphene powder and hollow nano zinc powder under protective gas.
[0015] By adopting the above technical solution, epoxy resin has good adhesion, chemical corrosion resistance and mechanical strength. As the main film-forming substance in the coating, it can firmly adhere to the surface of the coated object to form a tough protective film, effectively preventing the invasion of corrosive media. It ensures that the coating can maintain good protective performance in various harsh environments and extend the service life of the protected object.
[0016] Graphene has a large specific surface area and good dispersibility. It can form a uniform physical isolation layer in the coating, effectively blocking the penetration of these corrosive media. As a filler, hollow nano zinc powder and graphene together form a dense coating structure, further enhancing the physical shielding performance of the coating. The presence of graphene can also enhance the mechanical strength and conductivity of the coating and improve the overall performance of the coating. In addition, due to the use of hollow nano zinc powder, while providing good anti-corrosion performance, the density of the hollow nano zinc powder is effectively reduced, thereby reducing the weight of the coating and reducing the risk of cracking of the coating due to excessive coating weight and uneven distribution of internal stress.
[0017] Optionally, the graphene-zinc composite powder is prepared by the following method:
[0018] Graphene powder and hollow nano-zinc powder were weighed in a mass ratio of 1:20, and added into a ball mill in turn. Ethanol and alumina powder were also added. The ball mill was evacuated and filled with nitrogen. After ball milling for 2-4 hours under the protection of nitrogen atmosphere, a slurry was obtained. The slurry was placed in a vacuum drying oven to dry. After complete drying, a graphene-zinc composite powder was obtained.
[0019] By adopting the above technical scheme, graphene powder and hollow nano zinc powder are ball-milled under the protection of nitrogen atmosphere, and ethanol and aluminum oxide powder are added, so that the graphene and zinc powder can be fully mixed. At the same time, the aluminum oxide powder forms an insulating film between the graphene and the zinc powder to prevent the occurrence of galvanic corrosion and avoid accelerating the corrosion rate of the zinc powder, thereby improving the stability and durability of the graphene-zinc composite powder and extending the service life of the coating.
[0020] Optionally, the alumina powder accounts for 5-10% of the mass of the graphene powder.
[0021] By adopting the above technical solution, alumina powder, as an insulating material, can block the direct transmission of electrons between graphene and zinc powder, preventing the occurrence of galvanic corrosion. At the same time, alumina has good mechanical strength and chemical stability, which can enhance the performance of the composite powder. Alumina powder can not only promote the maintenance of the excellent performance of graphene, but also prevent the corrosion of zinc powder, and improve the overall stability and durability of the coating.
[0022] Optionally, the hollow nano zinc powder is prepared by the following method:
[0023] (1) Using zinc powder as an evaporation source material, placing the zinc powder in an evaporation chamber of a PVD device, and placing the substrate material in a deposition chamber of the PVD device;
[0024] (2) After the PVD equipment is evacuated, the deposition process is carried out: the evaporation temperature is controlled to be 1000-1200°C and the deposition time is 2-2.5h. After the deposition is completed, the heating source is turned off, and the hollow nano zinc powder is separated from the substrate by mechanical scraping, and then the hollow nano zinc powder is cleaned and dried.
[0025] Optionally, the base material is a ceramic sheet, and the Ra value of the ceramic sheet surface is 0.1-1 μm.
[0026] By adopting the above technical solution, the ceramic sheet has good thermal stability, chemical inertness and surface flatness, and is suitable as a deposition matrix for hollow nano zinc powder. Its surface roughness Ra value is between 0.1-1μm, which can provide good zinc powder adhesion. It ensures the uniformity and stability of the hollow nano zinc powder during the deposition process and improves the quality and performance of the coating. At the same time, the chemical inertness of the ceramic sheet can avoid chemical reactions with zinc powder and ensure the purity of the hollow nano zinc powder.
[0027] Optionally, the filler is one or a combination of mica powder, talcum powder, and silica powder, and the particle size of the filler is 10-50 μm.
[0028] Optionally, the epoxy resin is a bisphenol A epoxy resin with an epoxy equivalent of 180-200 g / eq.
[0029] By adopting the above technical solution, bisphenol A epoxy resin is selected, which has good adhesion, chemical corrosion resistance and mechanical strength. The epoxy equivalent is limited to between 180-200g / eq, which can ensure the stable performance of the epoxy resin and good compatibility with other ingredients. The film-forming performance and protective performance of the coating are guaranteed, and the stability and durability of the coating are improved.
[0030] In the second aspect, the present application provides a method for preparing a novel graphene zinc composite heavy-duty anti-corrosion coating, using the following technical solution:
[0031] A method for preparing a novel graphene zinc composite heavy-duty anti-corrosion coating comprises the following preparation steps:
[0032] S1. Weigh epoxy resin, graphene-zinc composite powder, filler, dispersant, solvent and leveling agent according to weight ratio;
[0033] S2, adding epoxy resin to the solvent, stirring evenly to obtain a resin solution;
[0034] S3, adding graphene-zinc composite powder, filler and dispersant to the resin solution, stirring and dispersing at high speed for 1-2 hours to make the powder evenly dispersed in the resin solution, then adding leveling agent, and continuing stirring for 0.5-1 hour to obtain coating slurry;
[0035] S4. Grind the coating slurry to a fineness of 20 to 40 μm, and then filter to obtain a novel graphene zinc composite heavy-duty anti-corrosion coating.
[0036] In summary, this application has the following beneficial effects:
[0037] 1. Since the present application adopts the composite of graphene and hollow nano zinc powder, and the addition of alumina powder, the crack resistance of the coating is improved together. Hollow nano zinc powder has a lower density than solid zinc powder due to its internal hollow structure, so it can provide more surface area under the same mass, thereby playing a better anti-corrosion effect in the coating and reducing the overall weight of the coating. Lighter coatings help to reduce the internal stress concentration caused by excessive weight, thereby reducing the risk of coating cracking. The hollow structure of the nanometer level enables the zinc powder to be better dispersed in the coating and form a more uniform mixed system with the resin matrix. This uniform mixing helps to improve the flexibility of the coating, so that the coating can better absorb and disperse stress when subjected to external forces, and reduce cracking caused by stress concentration. Hollow nano zinc powder, due to its high specific surface area, can provide more zinc ion sources, thereby quickly forming a zinc salt layer when the coating is damaged, and enhancing the cathodic protection effect of the coating. This enhanced cathodic protection effect helps to extend the anti-corrosion life of the coating and reduce the cracking of the coating caused by corrosion.
[0038] 2. In the present application, it is preferred to add alumina powder during the preparation process of graphene-zinc composite powder. At the same time, alumina powder forms an insulating film between graphene and zinc powder to prevent the occurrence of galvanic corrosion and avoid accelerating the corrosion rate of zinc powder, thereby improving the stability and durability of graphene-zinc composite powder and extending the service life of the coating. At the same time, alumina has good mechanical strength and chemical stability, which can enhance the performance of composite powder. Alumina powder can not only promote the maintenance of the excellent performance of graphene, but also prevent the corrosion of zinc powder and improve the overall stability and durability of the coating. DETAILED DESCRIPTION
[0039] The present application is further described in detail below in conjunction with embodiments.
[0040] Preparation Example 1
[0041] (1) Preparation of hollow nano zinc powder:
[0042] The zinc powder was placed in the evaporation chamber of the PVD equipment, and a ceramic sheet (surface Ra value of 0.8 μm) was selected as the substrate material and placed in the deposition chamber. The PVD equipment was evacuated to a suitable vacuum degree, the evaporation temperature was controlled to 1100°C, and the deposition time was 2.2 hours. After the deposition was completed, the heating source was turned off, and the hollow nano zinc powder was separated from the substrate by mechanical scraping, and then the hollow nano zinc powder was washed with deionized water and then placed in a drying oven for drying.
[0043] (2) Preparation of composite powder:
[0044] Weigh 10g of graphene powder and 200g of hollow nano zinc powder. Prepare 2000mL of ethanol and 8% of the mass of graphene powder, i.e. 0.8g of alumina powder. Add graphene powder and hollow nano zinc powder to a ball mill in sequence, and then add ethanol and alumina powder. Vacuum the ball mill and fill it with nitrogen, and mill for 3h under nitrogen atmosphere. Discharge the material to obtain slurry, place the slurry in a vacuum drying oven to dry, and obtain graphene-zinc composite powder after complete drying.
[0045] Preparation Example 2
[0046] (1) Preparation of hollow nano zinc powder:
[0047] The zinc powder was placed in the evaporation chamber of the PVD equipment, and a ceramic sheet (surface Ra value of 0.6 μm) was selected as the substrate material and placed in the deposition chamber. The PVD equipment was evacuated to a suitable vacuum degree, the evaporation temperature was controlled to 1000 ° C, and the deposition time was 2.2 h. After the deposition was completed, the heating source was turned off, and the hollow nano zinc powder was separated from the substrate by mechanical scraping, and then the hollow nano zinc powder was washed with deionized water and then placed in a drying oven for drying.
[0048] (2) Preparation of composite powder:
[0049] Weigh 15g of graphene powder and 300g of hollow nano zinc powder. Prepare 2000mL of ethanol and 6% of the mass of graphene powder, i.e. 0.9g of alumina powder. Add graphene powder and hollow nano zinc powder to a ball mill in sequence, and then add ethanol and alumina powder. Vacuum the ball mill and fill it with nitrogen, and mill for 3.5h under nitrogen atmosphere. Discharge the material to obtain slurry, place the slurry in a vacuum drying oven to dry, and obtain graphene-zinc composite powder after complete drying.
[0050] Preparation Example 3
[0051] (1) Preparation of hollow nano zinc powder:
[0052] The zinc powder was placed in the evaporation chamber of the PVD equipment, and a ceramic sheet (surface Ra value of 0.9 μm) was selected as the substrate material and placed in the deposition chamber. The PVD equipment was evacuated to a suitable vacuum degree, the evaporation temperature was controlled to 1200°C, and the deposition time was 2 hours. After the deposition was completed, the heating source was turned off, and the hollow nano zinc powder was separated from the substrate by mechanical scraping, and then the hollow nano zinc powder was washed with deionized water and then placed in a drying oven for drying.
[0053] (2) Preparation of composite powder:
[0054] Weigh 20g of graphene powder and 400g of hollow nano zinc powder. Prepare 2000mL of ethanol and 10% of the mass of graphene powder, i.e. 2.0g of alumina powder. Add graphene powder and hollow nano zinc powder to a ball mill in sequence, and then add ethanol and alumina powder. Vacuum the ball mill and fill it with nitrogen, and mill for 4h under nitrogen atmosphere. Discharge the material to obtain slurry, place the slurry in a vacuum drying oven to dry, and obtain graphene-zinc composite powder after complete drying.
[0055] Preparation Example 4
[0056] A graphene-zinc composite powder, which is different from Preparation Example 3 in that zinc powder is directly used in the preparation process of the composite powder.
[0057] Preparation Example 5
[0058] A graphene-zinc composite powder, which is different from Preparation Example 3 in that zinc powder is directly used without adding alumina powder during the preparation of the composite powder. Example Example 1
[0059] A novel graphene zinc composite heavy-duty anti-corrosion coating, the raw material dosage of which is shown in Table 1, wherein:
[0060] The epoxy resin selected is bisphenol A epoxy resin with an epoxy equivalent of 190 g / eq.
[0061] The graphene-zinc composite powder is the graphene-zinc composite powder prepared in Preparation Example 1.
[0062] The filler is a mixture of mica powder and talc powder in a ratio of 1:1, and the particle size of the filler is 20-40 μm.
[0063] The dispersant used is a polyacrylate dispersant.
[0064] The solvent used is xylene.
[0065] The leveling agent is a silicone leveling agent.
[0066] Its preparation method is:
[0067] S1. Weigh epoxy resin, graphene-zinc composite powder, filler, dispersant, solvent and leveling agent according to the above weight ratio.
[0068] S2. Add epoxy resin to the solvent and stir evenly at an appropriate stirring speed to obtain a resin solution. The stirring speed is controlled at 300-500r / min.
[0069] S3, add graphene-zinc composite powder, filler and dispersant to the resin solution, start high-speed stirring, and disperse for 1.5 hours. The high-speed stirring speed can be set to 1300-1500r / min to evenly disperse the powder in the resin solution. Then add the leveling agent and continue stirring for 0.8h to obtain the coating slurry.
[0070] S4, grinding the coating slurry, using a sand mill or other equipment to grind the coating slurry to a fineness of 30 μm. Then, the ground coating slurry is filtered to remove possible impurities, and a novel graphene zinc composite heavy-duty anti-corrosion coating is obtained. Example 2
[0071] A novel graphene zinc composite heavy-duty anti-corrosion coating, the raw material dosage of which is shown in Table 1, wherein:
[0072] The epoxy resin is bisphenol A epoxy resin, and the epoxy equivalent is 180 g / eq. The graphene-zinc composite powder is the graphene-zinc composite powder prepared in Preparation Example 2; the other raw materials are the same as those in Example 1.
[0073] Its preparation method is:
[0074] S1. Weigh epoxy resin, graphene-zinc composite powder, filler, dispersant, solvent and leveling agent according to the above weight ratio.
[0075] S2. Add epoxy resin to the solvent and stir evenly at an appropriate stirring speed to obtain a resin solution. The stirring speed is controlled at 300-500r / min.
[0076] S3, add graphene-zinc composite powder, filler and dispersant to the resin solution, start high-speed stirring, and disperse for 1 hour. The high-speed stirring speed can be set to 1300-1500r / min to evenly disperse the powder in the resin solution. Then add the leveling agent and continue stirring for 0.5h to obtain the coating slurry.
[0077] S4, grinding the coating slurry, using a sand mill or other equipment to grind the coating slurry to a fineness of 20 μm. Then, the ground coating slurry is filtered to remove possible impurities, and a novel graphene zinc composite heavy-duty anti-corrosion coating is obtained. Example 3
[0078] A novel graphene zinc composite heavy-duty anti-corrosion coating, the raw material dosage of which is shown in Table 1, wherein:
[0079] The epoxy resin is bisphenol A epoxy resin, and the epoxy equivalent is 200 g / eq. The graphene-zinc composite powder is the graphene-zinc composite powder prepared in Preparation Example 3; the other raw materials are the same as those in Example 1.
[0080] Its preparation method is:
[0081] S1. Weigh epoxy resin, graphene-zinc composite powder, filler, dispersant, solvent and leveling agent according to the above weight ratio.
[0082] S2. Add epoxy resin to the solvent and stir evenly at an appropriate stirring speed to obtain a resin solution. The stirring speed is controlled at 300-500r / min.
[0083] S3, add graphene-zinc composite powder, filler and dispersant to the resin solution, start high-speed stirring, and disperse for 2 hours. The high-speed stirring speed can be set to 1300-1500r / min to evenly disperse the powder in the resin solution. Then add the leveling agent and continue stirring for 1 hour to obtain the coating slurry.
[0084] S4, grinding the coating slurry, using a sand mill or other equipment to grind the coating slurry to a fineness of 40 μm. Then filtering the ground coating slurry to remove possible impurities, and obtaining a novel graphene zinc composite heavy-duty anti-corrosion coating.
[0085] Table 1 Amount of each raw material used in Examples 1-3 (g)
[0086]
[0087] Comparative Example
[0088] Comparative Example 1
[0089] This comparative example is a graphene anti-corrosion coating prepared by the method of Example 1 with application number CN202311233919.0 and patent name A graphene anti-corrosion coating.
[0090] Comparative Example 2
[0091] The difference between a novel graphene-zinc composite heavy-duty anti-corrosion coating and Example 1 is that the graphene-zinc composite powder is the graphene-zinc composite powder prepared in Preparation Example 4.
[0092] Comparative Example 3
[0093] The difference between a novel graphene-zinc composite heavy-duty anti-corrosion coating and Example 1 is that the graphene-zinc composite powder is the graphene-zinc composite powder prepared in Preparation Example 5.
[0094] 1. Corrosion resistance test:
[0095] The coating water resistance, acid resistance and alkali resistance test were carried out according to GB / T9274-1988 standard. The coating neutral salt spray resistance test was carried out according to GB / T1771-2007 standard. The test results are shown in Table 2.
[0096] 2. Initial drying crack resistance test:
[0097] According to GB / T9779-2015 standard, axial flow fans were used for air supply. The test board was a NAFHV grade asbestos-free fiber cement board with a thickness of 4mm-6mm and a size of 600×400mm. The coating thickness was ≤1.5mm. The coated test board was placed on the test board rack in the wind tunnel, and the fan was started. The wind speed was controlled within 3m / s±0.3m / s using the air volume control device. The air drying time was 10h. When the time was up, the machine stopped automatically. The surface of the test board was tested for cracks. The test results are shown in Table 2.
[0098] Table 2 Test results of Examples 1-3 and Comparative Examples 1-3
[0099]
[0100] It can be seen from the test results that the graphene-zinc composite powder prepared by hollow nano zinc powder and alumina powder has significant advantages in the crack resistance of the coating. The coatings in Examples 1-3 did not show cracks in the initial drying crack resistance test, while cracks of varying degrees appeared in Comparative Examples 1-3. This shows that the addition of hollow nano zinc powder and alumina powder plays an important role in improving the crack resistance of the coating.
[0101] Hollow nano zinc powder has a lower density than solid zinc powder due to its internal hollow structure, so it can provide more surface area at the same mass, thereby achieving better anti-corrosion effect in the coating and reducing the overall weight of the coating. Lighter coatings help reduce internal stress concentration caused by excessive weight, thereby reducing the risk of coating cracking. The nano-scale hollow structure allows the zinc powder to be better dispersed in the coating and form a more uniform mixing system with the resin matrix. This uniform mixing helps to improve the flexibility of the coating, allowing the coating to better absorb and disperse stress when subjected to external forces, reducing cracking caused by stress concentration.
[0102] Comparing Example 1 with Comparative Example 3, in the preparation process of the composite powder in Comparative Example 3, zinc powder is directly used without adding alumina powder. Therefore, galvanic corrosion is easily formed between graphene and zinc powder in the later stage, which accelerates the corrosion rate of zinc powder, thereby affecting the overall corrosion resistance and durability of the coating.
[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A graphene zinc composite heavy anti-corrosion coating, characterized in that: The invention comprises the following raw materials in parts by weight: Epoxy resin 30-50 parts; 20-30 parts of graphene-zinc composite powder; 10-20 parts of filler; Dispersant 2-5 parts; 15-30 parts of solvent; 1-3 parts of leveling agent; The graphene-zinc composite powder is prepared by the following method: Graphene powder and hollow nano zinc powder were weighed at a mass ratio of 1:20, and added to a ball mill in turn. Ethanol and alumina powder were also added, wherein the alumina powder accounted for 5-10% of the mass of the graphene powder. The ball mill was evacuated and filled with nitrogen. After ball milling for 2-4 hours under the protection of nitrogen atmosphere, a slurry was obtained. The slurry was placed in a vacuum drying oven for drying. After complete drying, a graphene-zinc composite powder was obtained.
2. The graphene zinc composite heavy anti-corrosion coating according to claim 1, characterized in that: The hollow nano zinc powder is prepared by the following method: (1) Using zinc powder as an evaporation source material, placing the zinc powder in an evaporation chamber of a PVD device, and placing the substrate material in a deposition chamber of the PVD device; (2) After the PVD equipment is evacuated, the deposition process is carried out: the evaporation temperature is controlled to be 1000-1200°C and the deposition time is 2-2.5h. After the deposition is completed, the heating source is turned off, and the hollow nano zinc powder is separated from the substrate by mechanical scraping, and then the hollow nano zinc powder is cleaned and dried.
3. A graphene zinc composite heavy anti-corrosion coating according to claim 2, characterized in that: The base material is a ceramic sheet, and the Ra value of the ceramic sheet surface is 0.1-1 μm.
4. The graphene zinc composite heavy-duty anti-corrosion coating according to claim 1, characterized in that: The filler is one or a combination of mica powder, talcum powder and silica powder, and the particle size of the filler is 10-50 μm.
5. The graphene zinc composite heavy-duty anti-corrosion coating according to claim 1, characterized in that: The epoxy resin is a bisphenol A type epoxy resin with an epoxy equivalent of 180-200 g / eq.
6. A method for preparing a graphene zinc composite heavy anti-corrosion coating according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: S1. Weigh epoxy resin, graphene-zinc composite powder, filler, dispersant, solvent and leveling agent according to weight ratio; S2, adding epoxy resin to the solvent, stirring evenly to obtain a resin solution; S3, adding graphene-zinc composite powder, filler and dispersant to the resin solution, stirring and dispersing at high speed for 1-2 hours to make the powder evenly dispersed in the resin solution, then adding leveling agent, and continuing stirring for 0.5-1 hour to obtain coating slurry; S4. Grind the coating slurry to a fineness of 20 to 40 μm, and then filter to obtain the graphene zinc composite heavy-duty anti-corrosion coating.
Citation Information
Patent Citations
Preparation method of epoxy zinc / graphene heavy-duty anticorrosive coating
CN109836964A
Graphene anticorrosive paint
CN117363148A
Composite zinc powder graphene coating and preparation method thereof
CN108929620A
Production method of zinc-aluminum alloy-graphene composite powder material
CN115055687A
Graphene composite powder material and preparation method therefor
WO2015165287A1
